Associations between posttraumatic stress disorder symptoms and coping strategies among men with lower limb amputations - Vildžiūnaitė, Kristina; Šinkariova, Liuda (Psichologija, 2016)
Lower limb amputation is a traumatic event that often leads to a post-traumatic stress disorder (PTSD) and the experience of its symptoms. One of the factors that may help to reduce exposure of the disorder and its symptoms is adequate stress management. The aim of the study was to examine associations between posttraumatic stress disorder (PTSD) symptoms and coping strategies (social support, problem solving, avoidance, emotional discharge) among men with lower limb amputation.In this research, 92 men who suffered a lower limb amputation were examined. Two questionnaires were used in the study: 1. Coping with stress questionnaire, which is used to measure coping strategies (Valickas, Želvienė ir Grakauskas, 2010). This questionnaire measures emotional discharge, problem solving, social support and avoidance coping strategies. 2. The Impact of Event Scale-Revised (IES-R) is used to measure PTSD symptoms (Weis & Marmar, 1997, Lithuanian version Kazlauskas et al., 2006). PTSD symptoms are invasion, increased arousal and avoidance. Also, demographic questions were included in the research instrument. All respondents were interviewed in rehabilitation centres where they were getting medical care at that moment.In the beginning of the research, it was expected that the problem solving and social support coping strategies will predict lower amount of PTSD symptoms and avoidance, emotional discharge coping strategies will predict higher amount of PTSD symptoms. The results showed that emotional discharge coping strategy predict higher overall PTSD. Also, it was revealed that PTSD were predicted not only by a more frequent use of emotional discharge coping strategy, but also by older age. Other statistically significant relationships were not found.
Keywords: posttraumatic stress disorder symptoms; coping strategies; lower limb amputation